PET imaging of unruptured intracranial aneurysm inflammation (PET-IA) study: a feasibility study protocol - Laukka, Dan (BMJ Group, 2025)
Introduction: Positron emission tomography (PET) imaging can be used to evaluate arterial wall inflammation in extracranial vascular diseases. However, the application of PET imaging in unruptured intracranial aneurysms (UIA) remains unexplored. Our objective is to investigate feasibility of PET imaging using 18F-FDG and 68Ga-DOTANOC tracers to evaluate arterial wall inflammation in UIA.
Methods and analysis: This PET imaging feasibility study will enrol patients scheduled for surgical treatment of UIA. The study subjects will undergo PET imaging of the intracranial arteries within 1 month before planned surgery. The imaging protocol includes 18F-FDG PET MRI, MRA with gadolinium enhancement, and 68Ga-DOTANOC PET CT. The study will also involve preoperative blood samples, intraoperative cerebrospinal fluid (CSF) samples, and aneurysm sac biopsy. Planned sample size is at least 18 patients. Primary outcome is uptake of 18F-FDG or 68Ga-DOTANOC in intracranial arterial aneurysms compared with contralateral normal vessel as maximum standardised uptake value or target-to-blood pool ratio and correlation of uptake of 18F-FDG or 68Ga-DOTANOC to aneurysm histological findings. Secondary outcomes include estimating the correlations between uptake of 18F-FDG or 68Ga-DOTANOC and histological findings with blood and CSF miRNA-levels, arterial wall enhancement in gadolinium enhanced MRA, aneurysm size and shape, smoking, hypertension, and location of the aneurysm.
Ethics and dissemination: This study is approved by the Human Research Ethics Committee of the Hospital District of Southwest Finland, Finnish Medicines Agency Fimea, and Turku University Hospital. Findings will be disseminated through peer-reviewed journal articles and presentations at national and international conferences.